2019
DOI: 10.3329/birdem.v9i1.39725
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Serum Uric Acid Levels in Bangladeshi Gestational Diabetic Mothers Attending a Tertiary Care Hospital

Abstract: Background: The hyperuricaemia in gestational diabetes mellitus (GDM) has been explained to be a component of the metabolic syndrome which reflects insulin resistance. Gestational huperuricaemia was found to be significantly associated with a high rate of maternal and foetal complications along with proteinuria and hypertension. Aims of this study were to evaluate the serum uric acid levels in Bangladeshi women with GDM in their second and third trimesters of pregnancy. Methods: This descriptive cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Gestational diabetes mellitus (GDM) was not prospectively associated with first trimester maternal Se, Cu, Zn, and Fe levels [1,28]. In women with GDM (in retrospective studies), the relationships between higher levels of plasma Cu and GDM were found [17,18]. Retrospective studies indicate that there are discrepancies in the relationships between Fe, Se, and Zn, and GDM risk [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational diabetes mellitus (GDM) was not prospectively associated with first trimester maternal Se, Cu, Zn, and Fe levels [1,28]. In women with GDM (in retrospective studies), the relationships between higher levels of plasma Cu and GDM were found [17,18]. Retrospective studies indicate that there are discrepancies in the relationships between Fe, Se, and Zn, and GDM risk [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted earlier were mainly animal studies or retrospective studies in humans. Abnormal levels of Se, Fe, Zn, and Cu were found in women with preeclampsia or gestational diabetes mellitus (GDM) [16][17][18]. However, these effects may be due to disorders which have already developed, e.g., increased oxidative stress can increase the consumption of antioxidant elements.…”
Section: Introductionmentioning
confidence: 99%
“…Also the release of Zn from tissues may be depressed in OCP users. 11,23 Adequate Zn level is believed to be important in immune function. Zn exerts a number of indirect antioxidant functions and its deficiency can decrease the response to insulin, possibly by increased oxidative stress, apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Another study had revealed that there is pronounced alteration of serum Zn level in GDM cases compared to normal pregnancy. 9,11 Women on different contraceptive methods have been linked with the development of various diseases and possible changes in serum trace elements and vitamins of women on contraceptives have been postulated. [12][13][14] Alterations in metabolic processes and trace element profiles are governed by genetic disposition as well as environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…But the study of the correlation between serum zinc and GDM pathogenesis remains a source of controversy. For instance, certain articles report that GDM cases have decreased serum zinc levels relative to the normal pregnant women (Mishu et al, 2019), but others suggest no difference in serum zinc concentrations between GDM women and healthy pregnant women (Behboudi-Gandevani et al, 2013;Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%